2017
DOI: 10.1097/mph.0000000000000879
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Iron Sucrose for Children With Iron Deficiency Anemia

Abstract: Iron deficiency anemia (IDA) is the most common nutritional deficiency in children. Most children with IDA are treated with oral iron preparations. However, intravenous (IV) iron is an alternative for children with severe IDA who have difficulty in adhering to or absorbing oral iron. We sought to describe the safety and effectiveness of IV iron sucrose for treatment of IDA in children. Pharmacy records of children who received IV iron sucrose at a children's hospital between 2004 and 2014 were reviewed. Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…documented. A rise in posttreatment hemoglobin levels implies that erythropoietic recovery is achieved with intravenous iron sucrose which also 16,18 strengthens the findings of our study. The most common side effect in our study is fever 10% whereas the study by Mantadakis et al reported the most common adverse effect of parental iron to be injection site extravasation followed by a 19 transient alteration in taste.…”
Section: Table II :Feeding History and Diagnosis At The Time Of Admis...supporting
confidence: 88%
“…documented. A rise in posttreatment hemoglobin levels implies that erythropoietic recovery is achieved with intravenous iron sucrose which also 16,18 strengthens the findings of our study. The most common side effect in our study is fever 10% whereas the study by Mantadakis et al reported the most common adverse effect of parental iron to be injection site extravasation followed by a 19 transient alteration in taste.…”
Section: Table II :Feeding History and Diagnosis At The Time Of Admis...supporting
confidence: 88%
“…The majority of IV iron sucrose infusions were administered to patients with IBD, and it was reported that the treatment was safe and tolerable. [5][6][7]17,18 A small number of children experienced coughing, wheezing, or side effects that were not life-threatening and did not require hospitalization. 5,17 Mantadakis et al 19 reported mild side effects such as phlebitis at the infusion site.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, our study supports previously published data describing the use of IV iron sucrose in children. 9,11,12…”
Section: Discussionmentioning
confidence: 99%